Ay, Neferti, Nakhtmin and Ameny: Politics and Rhetoric at the End of the Eighteenth Dynasty - Lurson, Benoît (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
During his reign, King Ay had a speos built in Akhmim, known as the speos of el-Salamuni. Its façade displays a monumental inscription, which contains a long eulogy to the king uttered by the overseer of works, Nakhtmin. For the composition of this inscription, its author had recourse to the Prophecy of Neferti . This paper investigates the ways and means of this recourse. First, el-Salamuni’s inscription is transliterated, deconstructed, and translated. Then, locutions and verb forms belonging to the first part of the inscription and of the Prophecy of Neferti are compared. This comparison shows that whilst conceiving a unique text, the author of the inscription used locutions and verb forms specific to the Prophecy to compose a text structured like it, thereby allowing the reader to readily call the Prophecy to the mind. A lexical comparison of both texts completes this examination. Next, an investigation of Ay’s deeds related in the inscription reveals the importance of the notion of benefactions ( ȝḫ.t ), with the speos of el-Salamuni being an exemplification of what being ȝḫ means for the king. Furthermore, although Ay’s deeds praised by Nakhtmin in his eulogy look like a collection of random deeds, they do in fact illustrate different facets of the one pivotal and dominant deed that is central to Ay’s actions: the restoration of communication between the gods, the king and the people, for which purpose the speos happens to be a medium. This investigation also shows that by recourse to the Prophecy , Ay is made into a messianic king, likened to Ameny. Then, in order to explore the reason of the recourse to the Prophecy of Neferti , the speeches of Neferti and Nakhtmin are considered in relation to each other. Based on their common witnessing function, it can be deduced that the author of the inscription considered Neferti to be a true prophecy. This leads to the question of the genre of the Prophecy and of el-Salamuni’s inscription. It is proposed that the inscription is an epideictic text. For convincingly classifying el-Salamuni’s inscription as a rhetorical epideictic composition coming under the Aristotelian rhetoric, the essential features of this genre are sought. As a matter of fact, an audience, a kairos , an appropriate ethos for the speaker, an argumentation founded on the logos, but also a strong pathos, can be characterised. As for the thesis of the discourse, it is understood that if the communication with the gods is restored and if the people take advantage of it, it is thanks to Ay’s personal values. The temporality of Nakhtmin’s encomium, who relates events from his present, the focus of the text on virtue, as well as its dispositio , complete the list of the essential features of an epideictic composition. In conclusion, the notion of propaganda is reassessed, and el-Salamuni’s inscription as an epideictic text reinstated as a long-term socio-political discourse, as a composition admittedly aimed at establishing absolute confidence of the audience in Ay, but also at reinforcing social cohesion and cultural identity, a function probably required after the Amarna Period.